Infectious pancreatic necrosis virus (IPNV) recombinant viral protein 1 (VP1) and VP2-Flagellin fusion protein elicit distinct expression profiles of cytokines involved in type 1, type 2, and regulatory T cell response in rainbow trout (Oncorhynchus mykiss). Issue 131 (December 2022) - Wong-Benito, Valentina; Barraza, Felipe; Trujillo-Imarai, Agustín; Ruiz-Higgs, Daniela; Montero, Ruth; Sandino, Ana María; Wang, Tiehui; Maisey, Kevin; Secombes, Christopher J.; Imarai, Mónica
Abstract: In this study, we examined the cytokine immune response against two proteins of infectious pancreatic necrosis virus (IPNV) in rainbow trout ( Oncorhynchus mykiss ), the virion-associated RNA polymerase VP1 and VP2-Flagellin (VP2-Flg) fusion protein. Since VP1 is not a structural protein, we hypothesize it can induce cellular immunity, an essential mechanism of the antiviral response. At the same time, the fusion construction VP2-Flg could be highly immunogenic due to the presence of the flagellin used as an adjuvant. Fish were immunized with the corresponding antigen in Montanide™, and the gene expression of a set of marker genes of Th1, Th2, and the immune regulatory response was quantified in the head kidney of immunized and control fish. Results indicate that VP1 induced upregulation of ifn- γ, il-12p40c, il-4/13a, il-4/13b2, il-10a, and tgf- β1 in immunized fish. Expression of il-2a did not change in treated fish at the times tested. The antigen-dependent response was analysed by in vitro restimulation of head kidney leukocytes. In this assay, the group of cytokines upregulated after VP1-restimulation was consistent with those upregulated in the head kidney in vivo . Interestingly, VP1 induced il-2a expression after in vitro restimulation. The analysis of sorted lymphocytes showed that the increase of cytokines occurred in CD4-1 + T cells suggesting that Th differentiation happens in response to VP1. This is also consistent with the expression of t-bet and gata3, the master regulators for Th1/Th2 differentiation in the kidneys of immunized animals. A different cytokine expression profile was found after VP2-Flg administration, i.e., upregulation occurs for ifn- γ, il-4/13a, il-10a, and tgf- β1, while down-regulation was observed in il-4/13b2 and il-2a . The cytokine response was due to flagellin; only the il-2a effect was dependent upon VP2 in the fusion protein. To the best of our knowledge this study reports for the first-time characteristics of the adaptive immune response induced in response to IPNV VP1 and the fusion protein VP2-Flg in fish. VP1 induces cytokines able to trigger the humoral and cell-mediated immune response in rainbow trout. The analysis of the fish response against VP2-Flg revealed the immunogenic properties of Aeromonas salmonicida flagellin, which can be further tested for adjuvanticity. The novel immunogenic effects of VP1 in rainbow trout open new opportunities for further IPNV vaccine development using this viral protein. Highlights: The rainbow trout adaptive immune response against IPNV VP1 and VP2-Flagellin was studied. VP1 induces Th1 and Th2 type cytokines able to trigger the humoral and cell-mediated immunity in rainbow trout. CD4-1 + T cells produced most of the cytokines indicating that Th differentiation occurred in response to VP1. rVP1 in vitro stimulation of leukocytes revealed a different cytokine profiling in each fish. Trout response against VP2-Flg revealed the immunogenic properties of Aeromonas salmonicida flagellin.